PENGEMBANGAN DESAIN MOTIF DAN SISTEM PRODUKSI KERAJINAN KAIN (IJA) ACEH DI KECAMATAN SYIAH KUALA, KOTA BANDA ACEH - Wardiah, Wardiah (Universitas Muhammadiyah Aceh, 2009)
The empowerment of small handicraft industry is one of the government priority program aiming at developing the economy, thus included the pattern design industry of Acehnese cloth in Kota Banda Aceh. The fact shows that there are many obstacle in developing Acehnese art designed cloth industry; both are from the pattern design and production system applied. The long term goal is to improve the pattern design and the working efficiency of craft people in developing the business to be small industry business. Mean while, this project is aiming at finding out the ability of pattern design for various Acehnese cloth types during the production as well as identification of supporting factors and obstacles in improving the product. The primary data were obtained from female crafters for the purpose of making sample. The instruments used in gathering the data were interview and observation, where the data was analyzed by using qualitative approach. The result showed that the richness of pattern and ornamental design required further development in differnt area such variety of pattern design of Acehnese cloth, the building pattern, the kings head letters, traditional cloths an curves from the kings gravestone. As the improvement of art pattern design of Acehnese cloth, it is required that the products of Acehnese cloth not only intended for male or female wearing but also in form or sarong and curtain. Conclusion, the products of Acehnese cloth which made for pre clothing have Acehnese pattern design by high quality stamp batik work and draw batik. Key words: pattern design, Acehnese cloth, small industry DAFTAR PUSTAKA Dariyanto, 2003. Tehnik Pembuatan Batik & Sablon. Semarang: Aneka Ilmu. Dinas Pariwisata. 2005. Peranan Hasil Kerajinan sebagai Daya Pikat Pariwisata Budaya Aceh, Buletin Wisata Aceh. Dharsono, H. 1992. Seni Sulam. Jakarta: Embroidery Pustaka Kartini. Dekranas. 2005. Sekilas Sejarah Dewan Kerajinan Nasional. Jakarta. Gahauna, FE & Argianto, D. 2007. Sebuah Kajian Motif Ija Aceh dengan Teknik Batik sebagai Identitas Khas Masyarakat Nanggroe Aceh Darussalam. Banda Aceh. Husin Amir H. 2002. Ragam Hias 2 Motif Aceh. Banda Aceh: Dewan Kerajinan Nasional NAD. Koeswara, J. 1999. Program Pengembangan Budaya “Enterpreneur-ship” di Perguruan Tinggi dalam Manajemen Perguruan Tinggi Berwawasan Enterpreneurship. LP-3 UGM. Volume I. Yogyakarta. Leigh, B. 1989. Tangan-Tangan Terampil Seni Kerajinan Aceh. Terjemahan Latif Thayeb Tirto Sudiro. Jakarta: Djmbatan. Mukhirah. 2004. Pengembangan Kewirausahaan Pengrajin Wanita di sekitar Kampus Darussalan Unsyiah. Naskah Fotocopy Laporan Pengabdian kepada Masyarakat. Muriati, Cut dan A. Hamid Rasyid. 1998. Ragam Hias Aceh, Koleksi Mesium Negeri Provinsi Aceh, Banda Aceh. Departemen Pendidikan dan Kebudayaan Bagian Proyek Permeseuman Daerah Istimewa Aceh. Mulyanto. 1995. Peluang Kerja dan Berusaha di Pedesaan. BPFFE. Jakarta. Peneliti Balai Pelestarian Sejarah & Nilai-Nilai Tradisional Aceh, 200.”Sejarah motif-motif Kriya Aceh” Makalah Disajikan pada Seminar Bedah Motif Aceh, Balai Pelestarian Sejarah & Nilai-nilai Tradisional, Banda Aceh, 21-22 November. Serambi Indonesia. 2004. Profil Industri Kerajinan Batik Aceh. Edisi Februari. Setiawati, P. 2004. Kupas Tuntas Teknik Proses Membatik Dilengkapi Teknik Menyablon: Absolut. Syarif, S. 2000. Pekerja Wanita Industri Wanita di Propinsi Sumatera Barat. Pusat Peneliti Kependudukan Universitas Gajah Mada. Yogyakarta. Thursina. 2008. Desain Batik Motif Tradisional Aceh. Laporan Hasil Penelitian Unsyiah. Yahya, F. 1997. Beberapa Aspek yang Mempengaruhi Wanita Pekerja Rumahan di Kabupaten Aceh Besar. Naskah Fotocopy Laporan Hasil Penelitian Universitas Syiah Kuala. Walad Iskandar Muzakir, 2007,”Ragam Hias Aceh, Implementasi dan Pengembangan” Makalah disajikan pada Seminar Bedah Motif Aceh, 21-22 November.